Reliability assessment of localizing different subsurface utilities using geophysics measurement / Mohammad shahrulnizam ismail - ismail, Mohammad shahrulnizam (2023)
Uncertain depths of underground utility services necessitate the application of competent geophysical techniques to the mapping of underground utilities. However, the accuracy of this geophysical measurement is contingent upon the utility substance and soil characteristics with varying soil moisture. Thus, the aim of this study is to ensure that this geophysical device is capable of identifying a variety of utility substances with an appropriate level of accuracy under quality A. While the objective of the study is to localize multiple subsurface utilities in soils with varying moisture contents using geophysical approaches and to evaluate the accuracy of utility detection utilizing geophysical methods by employing alternative techniques compared to standard hyperbola fitting. In order to reach the objective, a simulation test facility for underground utility services has been established. A series of geophysical detection employing an Electromagnetic Locator (EML) and Ground Penetrating Radar (GPR) for varying percentages of moisture have been performed. Several processing and accuracy evaluations, including velocity determination and dielectric calculation, have been performed for GPR measurement, in contrast to the hyperbola fitting method. Root Mean Square Error (RMSE) was computed to identify the optimal method. A velocity estimate via dielectric calculation using Topp's formula for GPR detection exhibits a better accuracy analysis than typical hyperbola fitting with RMSEs of 0.05 and 0.08. The RMSE value for EML detection using the Direct Induction method is 0.25 for 0% soil moisture and 0.28 for 7.74% soil moisture, while the RMSE value for the direct connection method is 0.43 for 7.74% and 0% soil moisture. Direct Induction more effective detection than direct connection. Uncertain depths of underground utility services necessitate the application of competent geophysical techniques to the mapping of underground utilities. However, the accuracy of this geophysical measurement is contingent upon the utility substance and soil characteristics with varying soil moisture. Thus, the aim of this study is to ensure that this geophysical device is capable of identifying a variety of utility substances with an appropriate level of accuracy under quality A. While the objective of the study is to localize multiple subsurface utilities in soils with varying moisture contents using geophysical approaches and to evaluate the accuracy of utility detection utilizing geophysical methods by employing alternative techniques compared to standard hyperbola fitting. In order to reach the objective, a simulation test facility for underground utility services has been established. A series of geophysical detection employing an Electromagnetic Locator (EML) and Ground Penetrating Radar (GPR) for varying percentages of moisture have been performed. Several processing and accuracy evaluations, including velocity determination and dielectric calculation, have been performed for GPR measurement, in contrast to the hyperbola fitting method. Root Mean Square Error (RMSE) was computed to identify the optimal method. A velocity estimate via dielectric calculation using Topp's formula for GPR detection exhibits a better accuracy analysis than typical hyperbola fitting with RMSEs of 0.05 and 0.08. The RMSE value for EML detection using the Direct Induction method is 0.25 for 0% soil moisture and 0.28 for 7.74% soil moisture, while the RMSE value for the direct connection method is 0.43 for 7.74% and 0% soil moisture. Direct Induction more effective detection than direct connection.